Animacidade e o processamento de orações relativas de sujeito e objeto por bilíngues português-inglês - Guedes, Ramon Brasileiro (2021)
Due to their structural complexity, relative clauses have often been an object of study in psycholinguistics. Traditionally, subject relative clauses have been deemed easier to process than object relative clauses. This difference was supposedly due to the greater syntactic complexity of the latter. However, when the animacy in such structures is controlled, differences in processing cost between both types of relative clause disappear or are attenuated, which brings into question the idea that only syntactic factors are accessible to the parser during the initial stages of language processing. It is still not clear whether these results hold true in the case of second language processing. We decided to investigate if animacy interferes in the processing of English relative clauses by non-native speakers, in this case Brazilians who speak Portuguese as their mother tongue and English as their second language. Furthermore, we explored whether these participants’ English proficiency level would have any effect on the processing of relative clauses. With this goal in mind, we used a self-paced reading experiment with 32 Portuguese (L1)/English (L2) bilinguals, equally divided into two groups according to their proficiency level in the L2 (intermediate or advanced). The stimuli that we used were subject and object relative clauses, with either animate or inanimate referents, which generated four experimental conditions. The results that we obtained were compared with our corpus of English relative clauses. We observed the disappearance of the processing asymmetry between subject and object relative clauses in the case of highly proficient speakers, as well as a clear correlation between the sentence types most easily processed by this group and the most common types of relative clauses in our corpus. Different data were gathered from the intermediate-level participants, which could suggest non-syntactic factors are not as readily available to them during the processing of their L2.